Desain Ulang Antarmuka Pengguna dan Pengalaman dengan Peningkatan Identitas Merek untuk Situs Web STMKG melalui Implementasi WordPress - Tonny Wahyu Aji; Ahmad Meijlan Yasir; Nardi; Sorfian; Agustina Rachmawardani; Marianus Carol Jehadun; Adi Widiatmoko Wastumirad; Edward Trihadi (Yayasan Kita Menulis - JoCPES, 2025)
This paper presents the redesign, rebuild, and rebranding of the official website of Sekolah Tinggi Meteorologi Klimatologi dan Geofisika (STMKG) using the WordPress content management system. The project aimed to modernize the institution’s digital presence by enhancing layout consistency, mobile responsiveness, and brand identity. A content audit was conducted to reorganize fragmented navigation and outdated information. The entire development was executed directly within WordPress using Elementor, enabling rapid prototyping without external wireframing tools. Key improvements include structured program sections, a modern news layout, and a standardized footer, all designed in line with STMKG’s visual identity. Performance optimization—though not the primary focus—involved basic caching, compression, and lazy loading, with assessments via GTmetrix indicating areas for future improvement. The project, completed by a sixth-semester cadet, highlights the feasibility of student-led web transformation initiatives within academic institutions. Positive stakeholder feedback confirmed improvements in usability, clarity, and institutional credibility. This work demonstrates the practical application of accessible web technologies to deliver scalable, branded, and user-centered digital solutions in educational settings.